Generalized Kohn-Sham schemes and the band-gap problem - Seidl, A.; Görling, Andreas; Vogl, Peter; Majewski, Jacek; Levy, Mel (Physical Review B, 1996)
As an alternative to the standard Kohn-Sham procedure, other exact realizations of density-functional theory (generalized Kohn-Sham methods) are presented. The corresponding generalized Kohn-Sham eigenvalue gaps are shown to incorporate part of the discontinuity Δ of the exchange-correlation potential of standard Kohn-Sham theory. As an example, a generalized Kohn-Sham procedure splitting the exchange contribution to the total energy into a screened, nonlocal and a local density component is considered. This method leads to band gaps far better than those of local-density approximation and to good structural properties for the materials Si, Ge, GaAs, InP, and InSb.